Metode Cerita Bergambar Penerapan Metode Cerita Bergambar pada Mata Pelajaran Pendidikan Kewarganegaraan di Kelas III SDN Citeureup 1: Indonesia - Dwiyanti, Latifah; Farhurohman, Oman (Pendagogia: Jurnal Pendidikan Dasar, 2022)
The problem in this study is the low interest in learning of class III students at SDN Citeureup 1 in the Citizenship Education (PKn) eye. This study aims to describe the application of the picture story method to civics subjects in class III SDN Citeureup 1. This research is a descriptive qualitative research. This research was carried out at SDN Citeureup 1. The time of the research was carried out on November 18, 2021. Data collection techniques were through observation, interviews, and document review. The results show that there is an interest in students taking part in lessons and being actively involved in learning. Suggestions for teachers are that the pictorial story method can be applied in schools so that students are happy and actively involved in learning.